Digital halal ecosystem development: Applications and institutions in Japan, 2010–2025 - Prima Gandhi; Muhammad Nasir; Triyanto (IPB University, 2025)
The development of digital halal applications and the institutional frameworks in Japan from 2010 to 2025 has been driven by the expanding Muslim community, comprising both residents and tourists, who require reliable digital access to halal products, restaurants, and other services. Therefore, this qualitative descriptive study conducted a literature review, application testing, and secondary data analysis from academic articles, association reports, and online sources to identify seven key halal applications in Japan, namely Halal Gourmet Japan, Halal Navi, Halal Japan, software Halal Japan, Shinjuku Halal Food, and eHalal. A comparative overview of their technological features was also presented, including barcode scanning, GPS integration, AI-based functions, and optical character recognition capabilities. Institutions such as the Japan Halal Association, Japan Islamic Trust, Japan Muslim Association, Nippon Asia Halal Association, Muslim Professional Japan Association, and the diaspora-led Halal International Trust Organization provided certification, standardization, and training, supported by government tourism initiatives since 2016. Ongoing challenges included fragmented certification standards in the absence of a national halal authority, data silos lacking AI and blockchain integration, and cultural adaptation within Japan’s non-Muslim majority, where halal was increasingly perceived as a hygienic lifestyle choice. These seven halal software applications contributed to tourism, economic growth, and community cohesion, positioning Japan as an inclusive halal model through government, private, and diaspora collaboration.